The Romantic Ethic in Outreach Work - Erik Henningsen (Sociétés et Jeunesses en Difficulté)
This article focuses on Norwegian outreach youth workers. To deal with the challenges involved in street work and other aspects of their daily work, youth workers rely on practical knowledge acquired in and through practice. As a corollary of this, youth workers tend to place a strong emphasis on informality and moral commitment as the critical features of their occupational role. The article criticises the “romantic ethic” which emanate from this attitude, and point to Hannah Arendt’s concept of solidarity and Richard Sennett’s concepts of respect and autonomy as alternative bases for professionalism in outreach youth work. A greater engagement with social scientific research and theory at the outreach youth work services is recommended, to improve the understanding of the complexities involved in their core activities.